Understanding the Relationship Between Visitor Behavior and Linkage Systems to Support Sustainable Tourism of the Jakarta Old Town Area - Ramadhani, Anindita; Yahya, Wisely; Cecilia Adriana, Martina; Supriatna, Yayat; Herika, Herika (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2026)
The Jakarta Old Town Area is a major urban heritage and tourism destination experiencing spatial management challenges due to concentrated visitor activities, particularly in Taman Fatahillah. This study analyzes the area’s linkage system based on visitor behavior mapping to understand patterns of spatial connectivity. A qualitative descriptive method was applied to observe visitor movements through weekend observations over two weeks, involving 20 respondents. Of these, 50% of respondents visited Taman Fatahillah, while 25% visited the Bahari Museum and 25% visited Sunda Kelapa Harbor. The research was to identify destination preferences, and classify the types of linkages among attraction points. The results indicate two dominant connectivity clusters. The Taman Fatahillah–Jakarta Kota Station cluster accounts for the most of visitor movements and demonstrates the highest linkage complexity, connecting up to seven tourist objects through multiple linkage types, including side, linear, axis, corridor, rhythmic, and structural linkages. More than 50% of visitors to Taman Fatahillah originated from Jakarta Kota Station, confirming its role as the primary access node. In contrast, the Bahari Museum and Sunda Kelapa Harbor form a cluster but is characterized by limited spatial reach, connecting only two objects and dominated by side and linear linkages. These findings show that areas with more diverse linkage elements attract higher visitor flows, while zones with simpler linkages remain underutilized. These results underscore the importance of strengthening physical and functional linkages to promote balanced spatial use and support sustainable urban heritage tourism in the Jakarta Old Town Area.